Dose‐finding study of linaclotide in Japanese patients with chronic constipation: A phase II randomized, double‐blind, and placebo‐controlled study. Issue 12 (7th August 2018) - Fukudo, Shin; Miwa, Hiroto; Nakajima, Atsushi; Kinoshita, Yoshikazu; Kosako, Masanori; Nakagawa, Ayako; Akiho, Hiraku; Kuroishi, Kentaro; Johnston, Jeffrey M.; Currie, Mark; Ohkusa, Toshifumi
Abstract: Background: Based on the previous phase II/III studies of irritable bowel syndrome with constipation (IBS‐C) in Japan that demonstrated the efficacy and safety of linaclotide 0.5 mg/d, we evaluated linaclotide at doses of 0.5 mg/d and lower in the treatment of Japanese patients with chronic constipation (CC). Methods: This was a phase II randomized, double‐blind, placebo‐controlled, dose‐finding study of linaclotide for Japanese patients with CC (n = 382, 64 men, 318 women, age 20‐75). After a baseline period of two weeks, patients were randomized to receive placebo (n = 80), or 0.0625 mg (n = 82), 0.125 mg (n = 71), 0.25 mg (n = 73) or 0.5 mg (n = 76) of linaclotide during a two‐week treatment period. The primary efficacy endpoint was change from baseline in weekly spontaneous bowel movement (SBM) frequency during the first week. Secondary endpoints included complete SBM (CSBM) responder rates and IBS‐QOL. Safety and adverse events were also evaluated. Key Results: The change in SBM frequency during the first week (mean) was 3.89, 3.11, 3.87, and 3.85 for 0.0625 mg, 0.125 mg, 0.25 mg, and 0.5 mg for linaclotide, significantly higher than for placebo (1.91, P  < 0.05). The CSBM responder, which is an important parameter, showed the greatest improvement at the 0.5 mg during the 2 week. The most frequent adverse event in the linaclotide groups was diarrhea. Conclusions & Inferences: Our results suggest that 0.0625, 0.125, 0.25, and 0.5 mg/d are effective doses of linaclotide for treating CC in Japanese patients. ClinicalTrials.gov: NCT02425722, supported by Astellas Pharma, Inc. Abstract : This was a phase II randomized, double‐blind, placebo‐controlled, dose‐finding study of linaclotide for Japanese patients with CC (n = 382, 64 men, 318 women, age 20‐75). The change in SBM frequency during the first week (mean) was 3.89, 3.11, 3.87, and 3.85 for 0.0625 mg, 0.125 mg, 0.25 mg, and 0.5 mg for linaclotide, significantly higher than for placebo (1.91, P  < 0.05). The CSBM responder, which is an important parameter, showed the greatest improvement at the 0.5 mg during the 2 week.